An Empirical Study On The Regulatory Framework Of Strategic Alliance For SMES In Malaysia - Mohammadi Poorangi, Mehdi (2009)
This study addressed the concept of strategic alliance amongst Malaysian SMEs in different industries and tried to create a regulatory framework for the SME strategic alliance in Malaysia form a holistic view based on the statement of the sampled SMEs' esecutives.